Canola Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Shoup, Douglas; Stamm, Michael J. (My University, 2012)
This publication contains information for a projected budged reflecting expected income and cost based on canola production practices in south central Kansas.
MF2421_2012_12
Keywords: MF2421; Crops; Economics; MF